The Interplay of Transactional Leadership, Adaptive Culture, Work Motivation and Performance of Employees - Alfian Rendra Palefi; Tri Siwi Agustina; Muhebulah Jamali (Faculty of Education Universitas Negeri Malang, 2024)
This study aims to theoretical contribution for development concept of leadership factors and organizational culture factors in influencing work motivation and its implications for improving employee performance. A total of 150 questionnaires were distributed to employees of production division of PT X ,Tbk by purposive sampling, then data was processed using structural equation modeling using AMOS 23 application. Results showed that transactional leadership has a positive and significant effect on employee performance, adaptive culture has a positive and significant effect on employee performance, transactional leadership has a significant effect on employee performance with work motivation as mediation, and adaptive culture has a significant and positive effect on employee performance with work motivation as mediation.